Structure of the spermatheca in five families of isoptera - Costa-Leonardo, Ana Maria [UNESP]; Patricio, Gleiciani Bürger [UNESP] (My University, 2005)
The structure of the spermatheca was investigated in specimens of five termite families with the aid of light microscopy. In longitudinal section, the spermatheca of Zootermopsis nevadensis (Termopsidae) showed the shape of an umbrella with a secretory portion and duct. The other termite species, which belong to the families Kalotermitidae, Serritermitidae, Rhinotermitidae and Termitidae showed a spermatheca constituted only by the secretory portion. This structure was an elongate, fingerlike tube with a recurved and blind extremity. The spermatheca wall was composed of a single epithelium formed by class 3 secretory cells with a lumen lined by cuticle. The cuticle was thin and smooth or thick with digitiform projections in the species examined. All the termite females showed bundles of musculature outside of the spermatheca.
Keywords: Histology; Reproductive system; Sperm storage; Spermatheca; Termite; Isoptera; Kalotermitidae; Rhinotermitidae; Serritermitidae; Termitidae; Termopsidae; Zootermopsis nevadensis